Emicizumab‐mediated haemostatic function in patients with haemophilia A is down‐regulated by activated protein C through inactivation of activated factor V. (20th August 2018) - Yada, Koji; Nogami, Keiji; Shinozawa, Keiko; Kitazawa, Takehisa; Hattori, Kunihiro; Amano, Kagehiro; Fukutake, Katsuyuki; Shima, Midori
Summary: Activated protein C (APC) inactivates activated factor V (FVa) and moderates FVIIIa by restricting FV cofactor function. Emicizumab is a humanized anti‐FIXa/FX bispecific monoclonal antibody that mimicks FVIIIa cofactor function. In recent clinical trials in haemophilia A patients, once‐weekly subcutaneous administration of emicizumab was remarkably effective in preventing bleeding events, but the mechanisms controlling the regulation of emicizumab‐mediated haemostasis remain to be explored. We investigated the role of APC‐mediated reactions in these circumstances. APC dose‐dependently depressed thrombin generation (TG) initiated by emicizumab in FVIII‐deficient plasmas, and in normal plasmas preincubated with an anti‐FVIII antibody (FVIII‐depleted). FVIIIa‐independent FXa generation with emicizumab was not affected by the presence of APC, protein S and FV. The results suggested that APC‐induced down‐regulation of emicizumab‐dependent TG was accomplished by direct inactivation of FVa. The addition of APC to emicizumab mixed with FVIII‐depleted FV‐deficient plasma in the presence of various concentrations of exogenous FV demonstrated similar attenuation of TG, irrespective of specific FV concentrations. Emicizumab‐related TG in FVIII‐depleted FVLeiden plasma was decreased by APC more than that observed with native FVLeiden plasma. The findings indicated that emicizumab‐driven haemostasis was down regulated by APC‐mediated FVa inactivation in plasma from haemophilia A patients without or with FV defects.